The SISPI: A Model for Healing Without Imposing (Universitas Científica, 2026)
Researchers from Universidad Pontificia Bolivariana (UPB) worked alongside Indigenous communities in Chocó to design an intercultural health model that recognizes ancestral medicine as an integral part of the national healthcare system.